Axiological potential development model and its implementation in digital educational environment of a technical university (Revista de Investigaciones Universidad del Quindío, 2022)
Nowadays, it seems necessary to study the axiological potential of students in the digital educational environment of a technical university. This study, conducted on the basis of the experimental sites of the Federal State Budgetary Educational Institution of Higher Education, offers the model for the axiological potential development among students and its implementation in the digital educational environment of a technical university. The axiological potential of technical university students is manifested in the value attitude to educational and research activities, awareness of needs and opportunities, in the development of abilities to the level of productive activity, in the implementation of abilities and self-fulfillment. The article analyzes the model for student axiological potential development in the digital educational environment of a technical university, pays attention to methodological approaches, a set of pedagogical conditions for development and the structural-level content of axiological potential components among the students of a technical university.
Keywords: axiological potential; development model; technical university student; digital educational environment